30.4k views
0 votes
If f(x) = -3 and g(x) = 4x + 2x - 4, find (* + )(x).O A. 4x2 + x +1OB. 432 + x ->C.X2-12OD. 4x2+2x-7

User Danyim
by
5.2k points

1 Answer

1 vote

You have the following functions:


\begin{gathered} f(x)=(x)/(4)-3 \\ g(x)=4x^2+2x-4 \end{gathered}

In order to find (g + f)(x) add like terms of each function. Remind that like terms are those terms with the same variable and same exponent.

Then, you have:


\begin{gathered} (f+g)(x)=4x^2+2x+(x)/(4)-3-4 \\ (f+g)(x)=4x^2+(9)/(4)x-7 \end{gathered}

Hence, the answer is

4x^2 + 9/4 x - 7

User Gaurav Mishra
by
4.7k points